The effect of age and sex on the expression of GABA signaling components in the human hippocampus and entorhinal cortex - Jayarjun Ethiraj; Thulani Hansika Palpagama; Clinton Turner; Bert van der Werf; Henry John Waldvogel; Richard Lewis Maxwell Faull; Andrea Kwakowsky (Scientific Reports, 2021)
Abstract Gamma-aminobutyric acid (GABA) is the primary inhibitory neurotransmitter in the nervous system. The GABA signaling system in the brain is comprised of GABA synthesizing enzymes, transporters, GABAA and GABAB receptors (GABAAR and GABABR). Alterations in the expression of these signaling components have been observed in several brain regions throughout aging and between sexes in various animal models. The hippocampus is the memory centre of the brain and is impaired in several age-related disorders. It is composed of two main regions: the Cornu Ammonis (CA1-4) and the Dentate Gyrus (DG), which are interconnected with the Entorhinal Cortex (ECx). The age- and sex-specific changes of GABA signaling components in these regions of the human brain have not been examined. This study is the first to determine the effect of age and sex on the expression of GABA signaling components-GABAAR α1,2,3,5, β1-3, γ2, GABABR R1 and R2 subunits and the GABA synthesizing enzymes GAD 65/67-in the ECx, and the CA1 and DG regions of the human hippocampus using Western blotting. No significant differences were found in GABAAR α1,2,3,5, β1-3, γ2, GABABR R1 and R2 subunit and GAD65/76 expression levels in the ECx, CA1 and DG regions between the younger and older age groups for both sexes. However, we observed a significant negative correlation between age and GABAAR α1subunit level in the CA1 region for females; significant negative correlation between age and GABAAR β1, β3 and γ2 subunit expression in the DG region for males. In females a significant positive correlation was found between age and GABAAR γ2 subunit expression in the ECx and GABABR R2 subunit expression in the CA1 region. The results indicate that age and sex do not affect the expression of GAD 65/67. In conclusion, our results show age- and sex-related GABAA/BR subunit alterations in the ECx and hippocampus that might significantly influence GABAergic neurotransmission and underlie disease susceptibility and progression.